Hypercalcemia, an Important Puzzle Piece in Uncommon Onset Pediatric Sarcoidosis—A Case Report and a Review of the Literature - Cristina Oana Mărginean (Frontiers in Pediatrics, 2020)
Sarcoidosis (SD) is a systemic granulomatous condition that is especially encountered in young adults and rarely in children, affecting predominantly the lungs and lymph nodes. We report the case of a 14-year-old teenage boy admitted to our clinic for nausea, vomiting, and weight loss. Clinical examination at the time of admission revealed malaise, pallor, and abdominal tenderness in the epigastric area at palpation. Laboratory tests revealed an elevated level of hemoglobin, mild thrombocytosis, increased erythrocyte sedimentation rate, and a mild increase in creatinine and urea levels along with hypercalcemia. An abdominal ultrasound revealed a right ectopic kidney, whereas the upper digestive endoscopy showed intense hyperemia and edema of the gastric mucosa. Thoracic computed tomography scan revealed giant hilar and mediastinal lymphadenopathy, along with multiple micronodules within the lung parenchyma and ground-glass aspect. The level of angiotensin-converting enzyme was high, parathormone was normal, and vitamin D level was low. Pathological examination of the bronchial, mediastinal, and lung biopsies established the diagnosis of SD. We administered oral corticosteroids for 2 months with outstandingly favorable outcome and no signs of recurrence 6 months after the cessation of the therapy.